The Relationship between Self-Control and Problematic Internet Use with Phubbing in Emerging Adults - Chairunissa, Jesenia; Hastuti, Rahmah (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
This study aims to determine the relationship between self-control, problematic internet use (PIU), and phubbing behaviour in emerging adults or early adults aged 18-29. Self-control is regulating thoughts, emotions and behaviour to achieve long-term goals. Meanwhile, PIU is an excessive use of the internet that negatively affects mental well-being and social functioning. Phubbing ignores others because they are too focused on cell phones or the internet. The sample selection used a probability sampling technique, with a stratified random sampling method, involving 425 participants, 255 female participants and 170 male participants. The measuring instruments used in this study were the Brief Self-Control Scale (BSCS), Problematic Internet Use Questionnaire (PIUQ), and Generic Scale of Phubbing (GSP). This study has correlation results between variables with a p-value <0.001, which shows that self-control plays a role in reducing PIU and phubbing behaviour and indicates that PIU and phubbing are closely related. Conducting this study can help develop interventions to increase self-control and reduce the negative impact of PIU and phubbing on emerging adults or individuals who are in the early adult phase.